Community gardening during times of crisis: Recommendations for community-engaged dialogue, research, and praxis - Mejia, Angie; Bhattacharya, Manami; Nigon-Crowley, Amanda; Kirkpatrick, Kelly; Katoch, Chandi (Journal of Agriculture, Food Systems, and Community Development, 2020)
Using ongoing reflections from our recent work as members of a community gardening initiative, we outline relevant priorities for researchers, policymakers, and community practitioners to examine the role of community gardens in addressing the effects of COVID-19 on the lives of intersectionally diverse growers. To understand how COVID-19 has influenced the practices of community-led urban agricultural spaces, we suggest that future efforts take into consideration three essential areas of focus: uses of community gardening in combating food insecurity during a pandemic, changes in community garden operations in response to crises, and community gardening’s role in nurturing emotional well-being.